Taxonomic Study of the Brazilian Species of Charops Holmgren, 1859 (Ichneumonidae, Campopleginae) - Santos, Alvaro Doria dos (2018)
Parasitic insects are known for their distinct life strategy: they necessarily kill their hosts in order to complete their life cycle. Eighty percent of parasitoids species belongs to the order Hymenoptera (bees, ants and wasps). Among parasitoid wasps Ichneumonidae stands out with more than 25 thousand species and a great diversity of habits and hosts. Despite the large number of species already described, there is a low representativeness of species in tropical regions, mainly due to the lack of taxonomical studies in those areas. The objective of the present study was to compile the information on the biology of Ichneumonidae through an extensive literature review and to conduct a taxonomic study of the species of Charops Holmgren, 1859 (Campopleginae) occurring in Brazil. It was observed that out of the 950 species of Ichneumonidae registered in Brazil, less than 10% present some host records. These records are mainly concentrated in the south and southeast of the Brazil where the relatively largest number of taxonomists are concentrated. In addition, most of the records relate to hosts of economic importance in corn, soybean and cotton crops. Little is known about the parasitoid / host interaction in natural Brazilian biomes. Also, thirty-three species with dubious occurrence in Brazil were found. Notwithstanding Campopleginae being one of the subfamilies with the highest number of host records, taxonomical studies on it are still scarce in Brazil. An example is the genus Charops, which despite having recorded for Brazil at genus level, has never been studied through a taxonomic point of view. The study of 614 specimens of this genus revealed 9 new species from Brazil, being the first described for South America. Its geographical distribution record is expanded and illustrated in distribution maps. High resolution images and a key for these species are also provided.